On Future Pensions From the Second Pillar Pension Funds - Bartkus, Algirdas (Organizations and Markets in Emerging Economies, 2013)
The main focus of this paper lies in the possibility for particular second pillar pension funds participants to get a higher pension, compared with non-participants. These particular participants are the employees with average wages and average employment history. This analysis is of main importance when it comes to the decision to participate in the second pillar or not. Unit roots tests and cointegration analysis are used as the possible tools to investigate the dynamics of retirement income for participants and non-participants. This research has the intention to determine the conditions when replacement from the second pillar will offset the loss from pay-as-you-go system.
Keywords: second pillar pension funds; PAYG pensions; unit root tests; error correction model; cointegration